Study on pathogenicity of ORF virus strain UPM 1/14 and 2/14 in mice at different sites of inoculation with and without dexamethasone treatment - Tay, Kimmy. (2016)
Recently, two local ORFV strains (UPM 1/14 Malaysia; UPM 2/14 Malaysia) have been isolated. However, there is no study done in mice using these strains. This study aims to describe the effect of different ORFV strains and inoculation sites as well as dexamethasone effect on pathogenicity of ORFV in mice. Intradermal injection of 0.2ml 1% UPM 1/14 Malaysia (Group 1) and UPM 2/14 Malaysia (Group 2) were done in each group of 5 mice in Group 1 and Group 2 at dorsum (Group 1A; Group 2A), ear pinna (Group 1B; Group 2B) and labial commissure (Group 1C; Group 2C). Intradermal injection of 0.2ml 1% UPM 1/14 Malaysia was performed in dexamethasone group (n=5) and non-dexamethasone group (n=5). Mice in dexamethasone group were treated with dexamethasone, 5mg/kg/day, intraperitoneally three days prior to challenge and continued until day five post-challenge. In general, mild hyperaemia was observed in all treatment groups. There were no significant difference in mean lesion score among the groups of inoculation site (p>0.05) and between dexamethasone-treated group and non-dexamethasone group (p>0.05). Mice in Group 1 and Group 2 showed no significant difference in mean lesion score as well (p>0.05). However, mice in Group 2B and Group 2C had significantly higher mean stratum thickness (p<0.05). Overall histopathological examination revealed keratosis, acanthosis and ballooning degeneration. ORFV was detected by means of PCR on skin tissues of mice with skin lesions. In conclusion, intradermal inoculation of both local strains is able to produce mild skin lesion and histopathological changes in mice. Besides, there is no significant effect of variation in inoculation sites on pathogenicity of ORFV in mice model. In this study, dexamethasone has no statistical effect on pathogenicity of ORFV. Therefore, alternative drug such as cyclosporine can be used for further studies on this aspect.